1998
DOI: 10.1159/000007121
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of <i>Pseudomonas aeruginosa</i> in Intensive Care Units: Clusters of Nosocomial Cross-Infection and Encounter of a Multiple-Antibiotic Resistant Strain

Abstract: Serogrouping (determination of O antigens) and bacteriocin typing (based on susceptibility to one or more of 18 bacteriocins) were employed to survey 210 isolates of Pseudomonas aeruginosa from 201 patients in 8 intensive care units (ICU) during an observation period of 18 months. Eighty-eight isolates (41.9%) were nonserogroupable (NT); most common were serogroups O1, O9, O11, and O3. All except 5 isolates (97.6%) were bacteriocin-typable. However, phenotypic variation of bacteriocin susceptibility, in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…The clinical relevance of multidrug-resistant P. aeruginosa has recently been stressed by reports of nosocomial infections and outbreaks in several countries (1,22,32). Our report, together with more limited observations from Belgium (6), indicates that the bla PER-1 gene and associated resistance determinants may become an emerging therapeutic problem in Europe.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The clinical relevance of multidrug-resistant P. aeruginosa has recently been stressed by reports of nosocomial infections and outbreaks in several countries (1,22,32). Our report, together with more limited observations from Belgium (6), indicates that the bla PER-1 gene and associated resistance determinants may become an emerging therapeutic problem in Europe.…”
Section: Discussionmentioning
confidence: 58%
“…Southern blot hybridization was carried out using nitrocellulose membranes (Schleicher & Schuell). The probe used in filter hybridization experiments was a PCR-generated amplicon comprising the entire bla PER-1 open reading frame (19) labeled with 32 P by the random priming technique (24). PCR amplification of bla PER alleles was performed as described previously (24) on crude DNA extracts (prepared by boiling cells for 10 min in distilled water).…”
Section: Methodsmentioning
confidence: 99%
“…Eleven studies included non-fermenting Gram-negative isolates originating from France [9,10,12,15,20,[23][24][25][26]28,29], three studies included isolates originating from Japan [11,17,18], two from Italy [19,30] and one each from Thailand [16], Taiwan [14], Greece [8], Spain [27], the UK [22], Germany [21] and Bulgaria [13]. Fifteen of the twenty-three studies reported on the site of isolation of the isolates examined [9,10,12,13,15,[17][18][19][20][21]23,25,26,29,30].…”
Section: Microbiological Studiesmentioning
confidence: 99%
“…Although susceptibility tests provide profiles that are used in infection control, in most cases these data cannot confirm clusters of nosocomial cross-infection or distinguish unrelated infections (5,(7)(8)(9), especially when multiresistant strains are analyzed (6,10). However, quantitative analysis of antibiograms by comparing disk zone sizes has been considered useful for nosocomial infection control in a few situations (11).…”
Section: Introductionmentioning
confidence: 99%